Grocery budget planner using barcode / Zhariif Arzaq Zulkfly - Zulkfly, Zhariif Arzaq (Faculty of Computer and Mathematical Sciences, 2019)
Cash management, savings, planning for retirement and setting financial goals. is becoming increasingly important for the survival and well-being of our families. People have long desired greater control over their finances. People with a financial plan tend to save more money, feel better about their progress, and make more appropriate decisions. People in different positions needs to see all their accounts in one place in real time, track and analyze their spending, and achieve their financial goals. Budgeting will enable them actually reach their financial targets and set goals. A well thought out, planned and realistic budget will serve as a roadmap to get a person there. Budgeting is a financial tool facilitating their financial dreams, goals and aspirations.This project use waterfall methodology includes information gathering, planning, design, development, and testing in order to make this project work properly according to plan. Completion of the project is depend on the usability and accuracy testing that was conducted. The result of 23 respondents shows that majority of the respondents is satisfied and agree of how easy it is to use the mobile application. This application provide much better platform for people to plan for budgeting.